2018
DOI: 10.19082/7224
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and psychological impact of Acne vulgaris among female secondary school students in Arar city, Saudi Arabia, in 2018

Abstract: BackgroundAcne vulgaris is a common heath problem affecting adolescents with considerable impact on their quality of life.ObjectiveTo determine the prevalence of Acne vulgaris and its psychological impact among female secondary school students.MethodsA cross-sectional study was conducted during the period from January to March 2018, among all female secondary school students in 3 randomly selected schools, in Arar city (Saudi Arabia). The participants were clinically examined by a dermatologist to identify acn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 24 publications
(63 reference statements)
8
43
1
Order By: Relevance
“…The face was the most commonly involved site of acne in our study, with 68.9% of lesions involving this area of the body. Alanazi et al also reported the presence of acne lesions on the face in the majority of secondary school students [10]. The practice of self-medication was significantly more common in students having lesions on the face.…”
Section: Discussionmentioning
confidence: 99%
“…The face was the most commonly involved site of acne in our study, with 68.9% of lesions involving this area of the body. Alanazi et al also reported the presence of acne lesions on the face in the majority of secondary school students [10]. The practice of self-medication was significantly more common in students having lesions on the face.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects that the incidence of acne vulgaris is increasing in the Kingdom. Another study conducted in a nearby region of Northern Saudi Arabia, Arar, revealed 54% prevalence of acne among adolescents [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Since early 1900s, the association between acne and dietary habits has been questioned in the literature [14]. Literature showed enough epidemiological link to consider the effect of diet on acne [6,7]. Hence, studies have suggested dermatologists to encourage patients with acne to avoid refined carbohydrates and shift to low glycemic index foods [8].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas another community-based study carried out in China reported an acne prevalence of 38% among females aged 15-19 years [13]. A research carried out in Saudi Arabia found an overall prevalence of 14.3% among female secondary school students [14]. Most of these studies have been conducted in secondary school or high school students, with very few conducted in college and university students [4,12,15].…”
Section: Discussionmentioning
confidence: 99%